CONCRETIZE THE HANDLING AND PROTECTION OF REFUGEES ACROSS NATIONAL BORDERS IN INDONESIA - Respati Triana Putri; Febri Tursandi Ar-Rasyid (Polteknik Imigrasi, 2020)
This paper was written to find out the state of application of international legal instruments regarding refugee cases in a cross-brick country and to find out why there was a flow of refugees across Indonesian borders. By conducting studies in several libraries so that a written paper is created which has several important points, namely first, the State of Indonesia as a developing country does not have to justify the contents of the 1951 convention and the 1967 Protocol, because the Indonesian state has practiced the contents of the international agreements that have been mentioned. And refugees will continue to enter and make Indonesia a transit point to occupy destination countries that have been targeted by refugees. Second, cooperation between the Indonesian government and international institutions such as IOM and UNHCR is believed to be able to solve the problem of refugees which continues to be present in the territory of the State of Indonesia even though in practice it is often problematic in the realm of immigration because there is no governing law in Indonesia or the Indonesian authorities that determine it. Refugee status for those who enter Indonesian territory without holding official letters or documents related to entry into Indonesian territory. Therefore, the Immigration Service classifies them as legal immigrants if they are part of the refugees and cooperate with UNHCR, which is an international institution as a follow-up to determine the status of immigrants.